2020
DOI: 10.3390/ma13245712
|View full text |Cite
|
Sign up to set email alerts
|

MTA Enhances the Potential of Adipose-Derived Mesenchymal Stem Cells for Dentin–Pulp Complex Regeneration

Abstract: The aim of the current study was to investigate the effects of mineral trioxide aggregate (MTA) on the proliferation and differentiation of human adipose-derived mesenchymal stem cells (Ad-MSCs) as a surrogate cell source in futuristic stem-cell-based endodontic therapies. Human Ad-MSCs and mesenchymal stem cells derived from bone marrow (BM-MSCs) were isolated from liposuction waste adipose tissue and femur, respectively, and the effects of MTA-conditioned media on their viability, mineralization potential, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…However, many authors have studied the ability of ATSCs to differentiate into mineralizing cells for hard tissue regeneration such as bone [3] and dentine [24,32,33] . Some of these studies have revealed that ATSCs display an odontogenic potential in vitro [34] [35] , but the inductive stimulus required for odontogenic differentiation induction of ATSCs has not been fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…However, many authors have studied the ability of ATSCs to differentiate into mineralizing cells for hard tissue regeneration such as bone [3] and dentine [24,32,33] . Some of these studies have revealed that ATSCs display an odontogenic potential in vitro [34] [35] , but the inductive stimulus required for odontogenic differentiation induction of ATSCs has not been fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated cells were used as the positive control, while the treated ones with ice-cold methanol were used as the negative control. Finally, the fluorescence was measured using an excitation and emission wavelength at 530 nm and 580 nm, respectively [64,130]. The researchers also investigated the biocompatibility of GO and its impact on the proliferation of MSCs in the case of exposure at different alkaline environments [125,126].…”
Section: Graphene Family Combined With Human Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Untreated cells were used as the positive control, while the treated ones with ice-cold methanol were used as the negative control. Finally, the fluorescence was measured using an excitation and emission wavelength at 530 nm and 580 nm, respectively [64,130].…”
Section: Graphene Family Combined With Human Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations